“Porque não desejava criar filhos”: crime, maternidade e loucura no Rio Grande do Sul, década de 1920 - Tavares, Joanna Schmidt (Universidade do Vale do Rio dos Sinos, 2023)
This study aims to analyze the trajectory of a young woman who went through two state control institutions in Rio Grande do Sul in the 1920s: São Pedro Psychiatric Hospital and the Forensic Psychiatric Hospital. Using the interned woman's name as the guiding thread of the research, her criminal case file was located in the Public Archive of the State of Rio Grande do Sul (APERS). The young woman, a minor, of mixed race, and a cook on a farm in the city of São Gabriel, is accused of committing infanticide. By cross-referencing sources between her criminal case and a medical record, this work aims to reveal how legal and psychiatric discourses shaped the judgment of the defendant. It also seeks to understand how this process helps us comprehend the constructions of gender, class, race, motherhood, femininity, and madness in Rio Grande do Sul during the First Republic. Through the analysis of the case, we conclude that legal and medical knowledge positioned women as biologically more susceptible to mental instability. These spaces of internment for the insane and criminals, especially women deviating from expected feminine behavior, served as places for the reeducation of young women.
Keywords: Crime; Maternidade; Gênero; Loucura; Hospício São Pedro; Crime; Motherhood; Gender; Madness; São Pedro Psychiatric Hospital